Group B Streptococcal β-Hemolysin/Cytolysin Directly Impairs Cardiomyocyte Viability and Function - Hensler, Mary E. (Public Library of Science, 2008)
BACKGROUND: Group B Streptococcus (GBS) is a leading cause of neonatal sepsis where myocardial dysfunction is an important contributor to poor outcome. Here we study the effects of the GBS pore-forming β-hemolysin/cytolysin (Bh/c) exotoxin on cardiomyocyte viability, contractility, and calcium transients. METHODOLOGY/PRINCIPAL FINDINGS: HL-1 cardiomyocytes exposed to intact wild-type (WT) or isogenic Δβh/c mutant GBS, or to cell-free extracts from either strain, were assessed for viability by trypan blue exclusion and for apoptosis by TUNEL staining. Functionality of exposed cardiomyocytes was analyzed by visual quantitation of the rate and extent of contractility. Mitochondrial membrane polarization was measured in TMRE-loaded cells exposed to GBS βh/c. Effects of GBS βh/c on calcium transients were studied in fura-2AM-loaded primary rat ventricular cardiomyocytes. Exposure of HL-1 cardiomyocytes to either WT GBS or βh/c extracts significantly reduced both rate and extent of contractility and later induced necrotic and apoptotic cell death. No effects on cardiomyocyte viability or function were observed after treatment with Δβh/c mutant bacteria or extracts. The βh/c toxin was associated with complete and rapid loss of detectable calcium transients in primary neonatal rat ventricular cardiomyocytes and induced a loss of mitochondrial membrane polarization. These effects on viability and function were abrogated by the βh/c inhibitor, dipalmitoyl phosphatidylcholine (DPPC). CONCLUSIONS/SIGNIFICANCE: Our data show a rapid loss of cardiomyocyte viability and function induced by GBS βh/c, and these deleterious effects are inhibited by DPPC, a normal constituent of human pulmonary surfactant.. These findings have clinical implications for the cardiac dysfunction observed in neonatal GBS infections.